Identification Of Student Transferable Skills: Basis For Development Of Career Guidance Programs For Z Generation - Harum, Akhmad (Academic Journal of Psychology and Counseling, 2023)
A transferable skill is an ability that connects various skills, such as basic skills, digital skills, and specific skills of a job, in order to be successful in future work and life education. This study aims to identify the transferable skills of students of the Faculty of Education, Makassar State University, Guidance and Counseling study program as a basis for development in the generation Z career guidance program. The method used in this research is descriptive quantitative. Data collection techniques using a transferable skills questionnaire. The sample for this study amounted to 222 students of the Guidance and Counseling Study Program, Faculty of Education, Makassar State University. The sampling technique uses simple random sampling The results of this study indicate that the description of transferable skills of students of the Faculty of Education, Makassar State University, is in the high category, with an average value in the aspect of communication skills (CS) of 27.086, the aspect of management skills (MS) of 33.775, the aspect of numerical skills (NS) of 18.869, the aspect of creativity skills (CRS) of 21.617, the aspect of social skills of 20.167, the aspect of critical thinking of 15.252, and the aspect of business skills of 20.536. So that from these results, transferable skills of students can be the basis for the development of generation Z career guidance programs and an effort to successfully transition from education to the world of work.